Visualizing the Adoption of Circular Economy Practices in Emerging Apparel Industry through Rich Picture - Sitio, Rike; Jahroh, Siti; Harianto, Harianto; Suprehatin, Suprehatin (Aptisi Transactions On Technopreneurship (ATT), 2026)
The study aimed to visualize and understand how circular economy practices had been adopted within emerging apparel industry by employing the Soft Systems Methodology (SSM) through Rich Picture analysis. Qualitative data were collected from interviews, focus group discussions, and policy document reviews. The study explored interactions among key stakeholders within the apparel industry ecosystem, which consisted of government institutions, apparel producers ranging from large brands to Small and Medium Enterprises (SMEs), associations, recyclers, and consumers. The analysis applied SSM through Rich Picture to visualize technological readiness, entrepreneurial innovation, stakeholder relationships, and socio-political dynamics that shape the adoption process. The finding revealed that the adoption of circular practices was still at an early and fragmented stage. Limited technological capacity, weak policy coordination, and unequal power relations between dominant brands and smaller producers created significant barriers to progress. Several emerging initiatives led by ethical brands and community-based recyclers demonstrated a growing entrepreneurial creativity and moral commitment toward sustainable production. The Rich Picture captured these dynamics visually, connecting technological constraints, regulatory gaps, and market perception that influenced the system’s current state. This study concluded that accelerating circular adoption required systemic collaboration among entrepreneurs, policymakers, and technology actors. By extending SSM to the context of sustainability-driven innovation, this research provided practical insights for policymakers and industry practitioners to strengthen technological capacity, financial incentives, and partnership mechanism in building a more circular and inclusive apparel ecosystem.